Extraction variables optimization on phenolics content and antioxidant activities of in-vitro propagated leaves of Curcuma caesia Roxb. using response surface methodology - Haida, Zainol; Ab Ghani, Sharin; Hakiman, Mansor (North Carolina State University, 2025)
Curcuma caesia Roxb. (Zingiberaceae) is one of the endangered species in the genus Curcuma that possesses numerous beneficial bioactive compounds that are responsible for various pharmacological properties including anti-cancer, anti-asthmatic, anti-diabetic, and others. In the past few years, the number of C. caesia plants was reported to have drastically decreased due to over-harvesting activity. To conserve this species, plant tissue culture method was used as a propagation tool for the mass production of C. caesia plantlets. Hence, this study aimed to optimize the extraction of phenolics content and antioxidant activities using response surface methodology. In this study, central composite design (CCD) was used to investigate the effects of three independent variables, namely solvent-solid ratio (mL/g), methanol concentration (%), and extraction temperature (°C), on phenolics content and antioxidant activities. Based on the results, the optimal extraction condition was achieved using 54.02 mL/g solvent-solid ratio, 70% methanol concentration, and 70 °C of extraction temperature.